Local Vibration Stimuli Induce Mechanical Stress-Induced Factors and Facilitate Recovery From Immobilization-Induced Oxidative Myofiber Atrophy in Rats - Usuki, Fusako; Fujimura, Masatake; Nakamura, Atsushi; Nakano, Jiro; Okita, Minoru; Higuchi, Itsuro (Frontiers in Physiology, 2019)
Muscle atrophy can be caused by unloading stress such as microgravity environments or cast immobilization. Therapies for such disuse muscle atrophy and their underlying mechanisms are incompletely understood. Here, we investigated the therapeutic effects of local vibration stimulation on immobilization-induced skeletal muscle atrophy. A rat model was made by placing the left hindlimb in a cast for one week, leading to oxidative myofiber atrophy without myopathic changes in soleus skeletal muscle. Vibration stimulus (90 Hz, 15 min) to the plantar fascia of the atrophic hindlimb was performed once a day using a hand-held vibration massager after removal of a cast at the end of the immobilization period. After two weeks, rats were dissected and quantitative analysis of the cross-sectional areas of soleus myofibers was performed. The results revealed that vibration induced significant recovery from disuse muscle atrophy, compared with untreated immobilized samples. Furthermore, vibration treatment suppressed the fiber transition from slow to fast fiber types compared with vibration-untreated immobilized samples. Western blotting analyses of mechanical stress-induced factors revealed that the expression of mechano-growth factor (MGF), systemic insulin-like growth factor I, and the mechanotransduction protein, Yes-associated protein 1 (YAP1), were decreased in untreated immobilized soleus muscle, whereas vibration stimulation restored their expression. No change in the level of phosphorylation of YAP1Ser127 was observed, leading to no change in p-YAP1/YAP1 ratio in vibration-treated immobilized soleus muscle. The results indicate that vibration stimulus is effective to restore immobilization-induced inactivation of YAP1 pathway. Phosphorylation of ERK 1/2, but not AKT, was enhanced in vibration-treated immobilized soleus muscle. Furthermore, vibration stimuli restored immobilization-induced downregulation of the paired box transcription factor, PAX7, a critical factor for regenerative myogenesis in muscle satellite cells. Our results indicate that cyclic vibration stimuli are effective in activating satellite cells and facilitate recovery from immobilization-induced oxidative myofiber atrophy through upregulation of MGF and YAP1.